Pediatric uveitis - João M. Furtado; Justine R. Smith (Journal of Family Medicine and Primary Care)
Up to 10% of uveitis cases occur in children, with notable implications due to the risk of chronicity and vision loss. It can result from infections, autoimmune and autoinflammatory diseases, trauma, or masquerade syndromes. Primary care providers are vital in early detection, symptom management, and timely specialist referral. Depending on the etiology, symptoms may include redness, pain, photophobia, vision changes, and sometimes more severe vision loss or intense pain. Conservative initial treatment may include pain relievers and corticosteroid eye drops. Specialist care involves a thorough ocular examination and diagnostic tests to identify the underlying cause. Treatment aims to control inflammation and preserve vision, often necessitating long-term medication, with compliance being crucial. In low-resource settings, telemedicine and generic drugs may be useful to manage costs. Preventative strategies focus on prenatal care to avoid congenital infections, and distinguishing uveitis from conditions like conjunctivitis is essential for proper treatment. Multidisciplinary care ensures comprehensive management of the child’s health. In summary, early intervention and a collaborative approach among healthcare providers are key to mitigating the impact of uveitis on a child’s life.